2019
DOI: 10.5658/wood.2019.47.5.597
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ammonium Persulfate Concentration on Characteristics of Cellulose Nanocrystals from Oil Palm Frond

Abstract: Cellulose nanocrystals (CNCs) were successfully isolated from oil palm fronds (OPFs) using different concentrations of ammonium persulfate (APS), and their characteristics were analyzed by Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM), X-ray diffraction (XRD) analysis, and thermogravimetric analysis (TGA). APS oxidation effectively isolated CNCs with rod-like morphology in nanometer scale. The dimensions of the CNCs decreased with increasing APS concentration. FTIR and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 42 publications
3
11
0
Order By: Relevance
“…These findings were in good agreement with the previous studies [30]. Using a similar method of APS oxidation, the crystallinity index of the resulting CNCs was higher (87.4%) compared to that of other CNCs extracted from other cellulose sources such as oil palm frond (52.4%) [23], balsa (57.6%) and kapok (60.7%) [29], recycled medium-density fiberboard (63%) [30], sugarcane bagasse (76.5%) [21], borer powder of bamboo (69.8%) [39], Miscanthus x. Giganteus (70%) [24], lemon seeds (74.4%) [25], and industrial denim waste (83%) [27]. However, it was lower than the value for cotton liner (93.5%) [36].…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopysupporting
confidence: 92%
See 3 more Smart Citations
“…These findings were in good agreement with the previous studies [30]. Using a similar method of APS oxidation, the crystallinity index of the resulting CNCs was higher (87.4%) compared to that of other CNCs extracted from other cellulose sources such as oil palm frond (52.4%) [23], balsa (57.6%) and kapok (60.7%) [29], recycled medium-density fiberboard (63%) [30], sugarcane bagasse (76.5%) [21], borer powder of bamboo (69.8%) [39], Miscanthus x. Giganteus (70%) [24], lemon seeds (74.4%) [25], and industrial denim waste (83%) [27]. However, it was lower than the value for cotton liner (93.5%) [36].…”
Section: Fourier Transform Infrared (Ft-ir) Spectroscopysupporting
confidence: 92%
“…The APS oxidation method has been applied to fabricate CNCs due to its simple one-step method and because it does not require pretreatment, has low toxicity and high solubility, and is cheaper [17]. CNCs have been successfully fabricated using the APS oxidation process from various cellulose-fiber-based materials, such as sugarcane bagasse pulp [21], cotton linters [22], an oil palm frond [23], Miscanthus x. Giganteus [24], lemon seeds [25], cotton pulp [26], and industrial denim waste [27]. The characteristics of the CNCs prepared with APS oxidation methods are strongly influenced by the oxidation parameters, such as the APS concentration, oxidation temperature, and oxidation time [19,23,[27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the oxidation of ammonium persulfate (APS) can fabricate carboxylated cellulose nanocrystals (CNCs–COOH) directly from the cellulose source without any chemical pretreatment as in TEMPO-mediated oxidation, which is often conditioned to CNC sulfate prepared by an acid hydrolysis process [ 27 ]. The APS oxidation was extensively applied for the fabrication of CNCs from various natural cellulose resources such as flax, hemp, triticale, microcrystalline cellulose (MCC), Whatman CF1 paper [ 30 ], cotton [ 34 , 35 ], oil palm frond [ 36 ], sugarcane bagasse pulp [ 37 ], industrial denim waste [ 38 ], recycled medium-density fiberboards (MDF) [ 27 ], and lemon seeds [ 25 ]. So far, no study on the fabrication of CNCs from PP fibers via APS oxidation has been reported.…”
Section: Introductionmentioning
confidence: 99%